Chirality‐Driven Transportation and Oxidation Prevention by Chiral Selenium Nanoparticles. (23rd January 2020) - Huang, Yanyu; Fu, Yuanting; Li, Mengting; Jiang, Dawei; Kutyreff, Christopher J.; Engle, Jonathan W.; Lan, Xiaoli; Cai, Weibo; Chen, Tianfeng
Abstract: The chirality of nanoparticles directly influences their transport and biological effects under physiological conditions, but the details of this phenomenon have rarely been explored. Herein, chiral GSH‐anchored selenium nanoparticles (G@SeNPs) are fabricated to investigate the effect of their chirality on their transport and antioxidant activity. G@SeNPs modified with different enantiomers show opposite handedness with a tunable circular dichroism signal. Noninvasive positron emission tomography imaging clearly reveals that 64 Cu‐labeled l ‐G@SeNPs experience distinctly different transport among the major organs from that of their d ‐and dl ‐counterparts, demonstrating that the chirality of the G@SeNPs influences the biodistribution and kinetics. Taking advantage of the strong homologous cell adhesion and uptake, l ‐G@SeNPs have been shown here to effectively prevent oxidation damage caused by palmitic acid in insulinoma cells. Abstract : Selen‐Nanopartikel, die mit Glutathion‐Enantiomeren (l ‐, d ‐ und dl ‐Formen) dekoriert sind, zeigen spezifische Biodistributionen in Mäusen, wie durch PET‐Bildgebung mit 64 Cu‐Radiomarkierung erimttelt wurde. Aus den Ergebnissen lässt sich extrapolieren, dass l ‐G@SeNPs durch Palmitinsäure verursachte oxidative Schäden verhindern, indem sie die Aufnahme in Insulinomzellen erleichtern.